Modified shuffled frog leaping algorithm for simulation capability scheduling problem. (1st January 2014) - Xiao, Yingying; Hu, Li Bo; Chai, Xudong
Based on the analysis of characteristics of simulation capability scheduling problem in cloud simulation platform, this paper gives its mathematical description and introduces a modified shuffled frog leaping (MSFL) algorithm to solve the above optimisation problem with multi-mode constraint. The MFSL introduces GA to code the feasible solution space. During the random execution of coding, decoding and mutation, it increases three layers of coding constraints including simulation capability, task logic and feasible mode, to ensure the randomness of the solving process in the controllable scope. Thus, it can reduce the search range of solution space, get rid of the meaningless illegal solution, and ultimately improve the convergence speed of the algorithm and avoid precocity.